Perbandingan tingkat keberhasilan implan antara osteogenesis distraksi dengan autogenous bone graft Ratio of successful rate of dental implan between distraction osteogenesis with autogenous bone graft - Irma Drismayanti; Sariatun T; A’la unas B; Muh. Ruslin; Eri H. Jubhari (Journal of Dentomaxillofacial Science, 2012)
Endosseous dental implants are the treatment of choice for restoring function and reconstructing most edentulousareas of the maxilla and mandible. One of the most common problems in oral implantology is insufficient bone heightbetween the alveolar ridge and the mandible canal, as a result of mandibular atrophy from edentulism. Generally,alveolar bone defects can be reconstructed by either distraction osteogenesis (DO)or autogenous bone grafting(ABG). This paper discussed implant successful rate in DO versus ABG. DO shows a higher successful rate of implantthan ABG with the result more esthetic, lower rate of infection and bone resorption, no pain at donor area, andrelatively uncomplicated.